Use of Social Media Instagram and Tiktok in Promoting Wedding Clothing Services - Zulfa Salsabila Manalu; Budi Santoso; Arif Aridansyah (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2026)
This study aims to analyze the use of social media, particularly Instagram and TikTok, as promotional tools for a wedding attire service business represented by the @RickyIDM account. The background of this research is driven by the rapid development of digital technology, which has shifted marketing strategies from conventional methods to digital-based approaches, especially through visually oriented social media platforms. This research employs a qualitative approach using a case study method. Data were collected through observation, in-depth interviews, and documentation involving account managers and consumers. The data analysis process was conducted through data reduction, data display, and conclusion drawing, supported by triangulation techniques to ensure data validity. The findings reveal that the utilization of Instagram and TikTok by @RickyIDM has significantly contributed to increasing brand awareness, audience engagement, and consumer trust. The implemented strategy reflects the concept of Integrated Marketing Communication (IMC), characterized by consistent and integrated messaging across platforms, as well as Social Media Marketing principles, including content creation, content distribution, interaction, and community building. However, several challenges were identified, such as dependency on digital trends and platform algorithms, as well as discrepancies between the visual expectations formed on social media and the actual service experience. In conclusion, social media plays a strategic role in enhancing the promotion of wedding attire services. Nevertheless, it requires adaptive, consistent, and data-driven content management to achieve optimal results.